Role of protease‐activated receptor‐1 (PAR‐1) in the glomerular filtration barrier integrity. Issue 15 (3rd August 2022) - Medipally, Ajay; Xiao, Min; Biederman, Laura; Satoskar, Anjali A.; Ivanov, Iouri; Rovin, Brad; Parikh, Samir; Kerlin, Bryce A.; Brodsky, Sergey V.
Abstract: Protease‐activated receptors (PAR) play an important role in the regulation of cellular function by the coagulation system, and they are activated by thrombin. PAR‐1 is expressed in both endothelial cells and podocytes in the kidney. The role of PAR1 in the maintenance of the glomerular filtration barrier is not clear. Anticoagulant‐related nephropathy (ARN) is a kidney disease with glomerular hematuria and red blood cell tubular casts. We validated 5/6 nephrectomy (5/6NE) in rats as a model of ARN and had demonstrated that direct thrombin inhibitor (dabigatran) induces ARN. The aim of this study was to investigate the role of PAR‐1 in the ARN pathogenesis. 5/6NE rats were treated with dabigatran (150 mg/kg/day), PAR‐1 inhibitor SCH79797 (1 and 3 mg/kg/day) and PAR‐1 agonist TFLLR‐NH2 (0.25 and 0.50 µmol/kg/day) for 7 days. Serum creatinine and hematuria were assessed daily. Kidney morphology was evaluated at the end of the study. In 5/6NE rats treated with either dabigatran or combination with a PAR‐1 modulator, there was an elevation in serum creatinine, glomerular hematuria, red blood casts in the tubules, and acute tubular epithelial cell injury. Interestingly, both PAR‐1 modulators in a dose‐depended manner had similar effects on the serum creatinine levels and hematuria as those of dabigatran. Dabigatran‐induced increase in the systolic blood pressure was not affected by PAR‐1 modulators. In conclusion, the normal function of PAR‐1 is crucial to maintain the glomerular filtration barrier integrity. Either activation or blockage of PAR‐1 leads to glomerular hematuria and subsequent acute tubular epithelial cell injury. Abstract : Red blood cell tubular casts in animals treated with PAR‐1 modulators with and without direct thrombin inhibitor dabigatran.